PREventive effect of FENestration with and without clipping on post-kidney transplantation lymphatic complications (PREFEN): study protocol for a randomised controlled trial - Golriz, Mohammad; Sabagh, Mohammad Sadegh; Mohammadi, Sara; Ghamarnejad, Omid; Khajeh, Elias; Mieth, Markus; Saeedi, Mohammed al; Diener, Markus K.; Mihaljevic, André Leopold; Morath, Christian; Zeier, Martin; Kulu, Yakup; et al. (BMJ open, 2020)
Introduction Peritoneal fenestration is an effective preventive method for reducing the rate of lymphatic complications in kidney transplantation (KTx). The size of the fenestration plays an important role in its effectiveness. A large peritoneal window is no longer indicated, due to herniation and difficulties in performing biopsies. Small preventive fenestration is effective but will be closed too early. The aim of this study is to evaluate whether metal clips around the edges of a small fenestration result in optimal effects with minimum fenestration size. - Methods and analysis This trial has been initiated in July 2019 and is expected to last for 2 and a half years. All patients older than 18 years, who receive kidneys from deceased donors, will be included. The kidney recipients will be randomly allocated to either a control arm (small fenestration alone) or an intervention arm (small fenestration with clipping). All fenestrations will be round, maximum 2 cm, and close to the kidney hilum. Clipping will be performed with eight metal clips around the peritoneal window (360°) in every 45° in an oblique position. The primary endpoint is the incidence of symptomatic post-KTx lymphatic complications, which require interventional treatment within 6 months after KTx. Secondary endpoints are intraoperative and postoperative outcomes, including blood loss, operation time, severity grade of lymphocele/lymphorrhea and relative symptoms. - Ethics and dissemination This protocol study received approval from the Ethics Committee of the University of Heidelberg (Registration Number S-318/2017). A Standard Protocol Items: Recommendations for Interventional Trials checklist is available for this protocol. The results will be disseminated through peer-reviewed journals and conference presentations. - Trial registration number ClinicalTrials.gov Registry (NCT03682627).